Discordance between pain and inflammation in rheumatoid arthritis - McWilliams, Daniel F. (2018)
Recent research interest has focused on the continuing problem of pain in RA. The long term prognosis for pain could be improved, even when inflammation is being suppressed. This talk will describe the progression of pain, and examine how factors other than inflammation may contribute to the prognosis of symptoms in people with RA. The DAS28 components have been used to try and quantify non-inflammatory pain mechanisms. The research examining this will also be summarised.